Study of the properties of high silicon aluminum alloy by laser welding - Yang, Dongsheng; Huang, Yilong (Frontiers in Materials, 2023)
High silicon aluminum alloy is a kind of high-performance electronic packaging material, due to its excellent thermal conductivity, low thermal expansion coefficient, and low density. The heat affected zone (HAZ) of conventional welding techniques is too wide to weld the high silicon aluminum alloy, as wide HAZ will improve risk of cracking. Laser welding with narrow HAZ, high joint strength, and good morphology, has been considered as a promising method to weld high silicon aluminum alloy. Herein, the surface morphology, microstructure, and microhardness of laser welding joint between Al-50wt.%Si and Al-27wt.%Si alloys were investigated. It has been found that welding speed at 3~5 mm/min can significantly reduce the hydrogen pores and cracks in laser welding joints. Also, the key paraments of laser welding to control the quality of joints are power and pulse width, while the former one is mainly controlling the joint width and the latter one is significantly changing the joint depth. Along the horizontal direction of laser welding joints, the microhardness increases firstly and then decreases, with the highest microhardness of 167 HV in the weld zone. Because the laser welding method could produce uniform microstructure of joints, the microhardness of joints is uniform along the longitudinal direction. The tensile properties of welding samples are almost the same with the properties of the Al-50wt.%Si base materials.